2015
DOI: 10.1111/soru.12091
|View full text |Cite
|
Sign up to set email alerts
|

Transition and Adaptation: An Analysis of Adaption Strategies Amongst Danish Farm Families from 1980–2008

Abstract: This article analyses how Danish farm families adapted to harsh and changing conditions in the period after the great western agricultural crisis in the early 1980s. Drawing on Bourdieu's concepts of habitus and adaptation, I analyse the creation and consolidation of different class fractions amongst farm families due to different adaptation strategies. The data contain information about the population of self-employed farmers and their families who were between 30-35 years old in 1980 (n = 9,123). Using seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The study revealed a web of context-linked features whose significance goes beyond the contingencies of individual trajectories. Indeed, the trajectories taken as a phenomenological lens [75] not only disclosed characteristics of the mainstream dairy context in line with previous studies on the agro-food sector [24,28,44,51,[54][55][56]81], but they also revealed the grip of the context on individual trajectories. The combined comprehension of the web of convergent and interconnected lock-ins and of the way actors managed to overcome lock-ins holds a significance that goes beyond the particular trajectories of actors.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The study revealed a web of context-linked features whose significance goes beyond the contingencies of individual trajectories. Indeed, the trajectories taken as a phenomenological lens [75] not only disclosed characteristics of the mainstream dairy context in line with previous studies on the agro-food sector [24,28,44,51,[54][55][56]81], but they also revealed the grip of the context on individual trajectories. The combined comprehension of the web of convergent and interconnected lock-ins and of the way actors managed to overcome lock-ins holds a significance that goes beyond the particular trajectories of actors.…”
supporting
confidence: 84%
“…The capability of farmers as a condition and driver for agency and change is a subject increasingly studied in the scientific literature. Capabilities are analyzed in terms of acquired skills [51] but also, in approaches inspired from constructivism [52], in terms of interactions and networks [53,54] and resilience [55,56]. One should also consider the context in which individuals evolve in order to understand how the agency may exert itself [30,36,48,[57][58][59][60].…”
Section: Changes In Trajectories May Face a Logic Of Inertia Inherentmentioning
confidence: 99%
“…On the other hand, literature reference emphasizes the adaptability of family farms in the course of time and in different forms of societies. 48 Overall, small enterprises have been assessed as having the potential to survive amidst rapid changes in the global world. 49 Human capacity is a crucial, fundamental element in the continuance of the farm enterprise.…”
Section: Discussionmentioning
confidence: 99%
“…Some of this came out when discussing landownership and access. Earlier, for instance, Michael was introduced, a 60‐something African American cooperative member who commented that since he is not rich “getting into farming is a damn‐near impossible nut to crack.” Comments like this, which at best gloss over the very real challenges that conventional growers face to acquire farmland and remain in agriculture (for a review of the farm transition and adaptation strategies, see Andrade ), miss the vulnerabilities faced by this group due to the productivist and individualist ideologies that have been linked to neoliberalism (see, e.g., Dibden, Potter, and Cocklin ; Glenna, Shortall, and Brandl ). In sum, while misrecognition was documented in comments made by North Dakota respondents concerning socially distant and historically marginalized “others” (as evidenced by Larry's comments that conclude the prior subsection), this was reciprocated by some in the urban cooperative, as in comments that appear to overstate some of the privilege held by those in conventional agriculture (I return to the subject of misrecognition momentarily).…”
Section: Comparing Cases: Discussion and Analysismentioning
confidence: 99%